The use of aquatic predators for larval control of mosquito disease vectors: opportunities and limitations - Dambach, Peter (Biological control, 2020)
Control efforts against the vectors of such tropical diseases as malaria, dengue, Zika, along with many others, have up to now relied heavily on the use of insecticides for both, vector and larvae control. Many of the insecticides used for the impregnation of bed nets, indoor residual spraying, fumigation, and treatment of larval breeding sites have already lost their effectiveness or are at risk of doing so. One opportunity that that has so far not been given priority in control programs has been the targeting of the vector larvae in their breeding habitats through the use of aquatic predators. The arsenal of aquatic predators consists of water living animals and the aquatic stages of many land-living or airborne animals. Many of these animal species are specialized in the predation of mosquito larvae or incorporate them as a major component of their diets. Habitat preferences of vector mosquito larvae and of aquatic predators are diverse and do not necessarily overlap, with the result that particular predator species may be the only viable agents against particular vector species. Despite encouragingly high predation rates achieved in laboratory experiments, the predatorś effectiveness in the field can differ remarkably. Also their use may result in negative impacts on ecosystems if not carefully attuned to the local food network. There is only limited evidence for any impact on actual disease transmission by means of larval control through aquatic predators. There is a need for more controlled field trials designed to register the changes achieved in adult mosquito abundance and the impact on human health, in order to be able to formulate clear health policy recommendations.